A retrospective analysis of the malaria trend in Yemen over the sixteen-years, from 2006 to 2021 - Wadhah Hassan Edrees; Wadee Abdullah Al-Shehari (BMC Public Health)
Abstract Background Malaria is one of the important diseases that threatens the global health system, especially in developing countries, including Yemen. Based on surveillance data, this analysis aimed to assess the trend of malaria in Yemen over the last sixteen years from 2006 to 2021. Methods A retrospective analysis was conducted on secondary malaria data from the database from the Ministry of Public Health and Population in Yemen. Results Of the 15,153,763 suspected cases, approximately 3,651,508 malaria cases were confirmed by both laboratory and clinical diagnoses. Plasmodium falciparum, P. vivax, mixed infections, P. malariae, and P. ovale were recorded at 1,118,117 (98.72%), 123,28 (1.10%), 1838 (0.16%), 155 (0.01%), and 30 (0.01%), respectively. Approximately 77.2% of all malaria cases were recorded in six governorates. Al Hudaydah recorded the highest number of malaria cases (1,231,294), followed by Hajjah (623,937), Taiz (450,051), Dhamar (167,399), Sa’adah (157,881), and Al-Mahweet (154,763). The overall incidence rate of malaria cases and P. falciparum, respectively, was 8.9 and 2.66 per 1,000 people. The highest mean incidence rate of malaria was recorded in Al Hudaydah, Hajjah, Al-Mahweet, Sa’adah, and Abyan, respectively, at 29.71, 19.49, 14.98, 10.62, and 10.14 per 1,000 people. Yemen reported 704 (0.02%) malaria death cases with an overall rate of case fatality of 0.03% and a mortality rate of 0.18 per 100,000 populations. The trend of case fatality decreased from 0.029% in 2006 to 0.015% in 2020, while the mortality rate per 100,000 individuals decreased from 0.3 in 2006 to 0.08 in 2021. Conclusion It currently suggests a continuous increase in the malaria burden without specifying trends or fluctuations and is becoming a public health threat and causing widespread concern. Therefore, the treatment and prevention of malaria infection are crucial for reducing mortality and complications by increasing the use of vector control tools and promoting early diagnosis and treatment.